Analysis of boiler tubes using gas tungsten arc welding in Grade 91 alloy steel. (2023) - Radhakrishnan, K.; Velusamy, B.; Saravanan, C.; Mohanraj, C.
Abstract: Failure analysis of Boiler components is an important step in the Inspection process of Boiler. If this is not taken sternly, it may lead to leakage or even bursting. So research works should be conducted to upgrade the quality of the material and ensure the effectiveness of the components like boiler tubes. In this paper an experiment is conducted by welding Grade 91 Alloy steel with proper process parameters. The joints are then subjected to Non– Destructive Testing and the final conclusion is discussed at the end. Grade 91 alloy seems to be suitable for boiler tube material. If applied proper welding techniques, an effective boiler tubes can be obtained.